2016
DOI: 10.1080/17474086.2017.1262758
|View full text |Cite
|
Sign up to set email alerts
|

How could patient reported outcomes improve patient management in chronic myeloid leukemia?

Abstract: Introduction: Patients reported outcome (PRO) are still under-used in patients with chronic myeloid leukemia (CML) treated with tyrosine kinase inhibitors (TKIs), though data on the correlation between quality of life (QoL) and therapeutic efficacy are increasingly known. Chronic low-grade toxicities can reduce patient's QoL and negatively impact on adherence. Areas covered: This review will focus on the role of QoL questionnaires in patients with CML, receiving imatinib or newer TKIs (dasatinib, nilotinib, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…The major outcomes were that none of our patients reported any significant side-effects despite the fact that the length of treatment was from 3-10 years with 90% having been treated for more than 6years. These outcomes are in agreement with a number of local reports from Saudi Arabia [4][5][6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Preparation Of Mononuclear Cells For Culture and Cfu-gm Cultursupporting
confidence: 81%
“…The major outcomes were that none of our patients reported any significant side-effects despite the fact that the length of treatment was from 3-10 years with 90% having been treated for more than 6years. These outcomes are in agreement with a number of local reports from Saudi Arabia [4][5][6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Preparation Of Mononuclear Cells For Culture and Cfu-gm Cultursupporting
confidence: 81%
“…Given the need for lifelong therapy, HRQoL from the patient perspective has become a key component of clinical decision-making [25], in addition to response to individual therapies. Although evaluation of HRQoL through PRO assessments in clinical trials for CML is limited [7], studies of bosutinib have routinely collected PRO data to assess the symptom burden and functional health status of patients [8][9][10][11]. In the phase 3 BFORE trial of bosutinib versus imatinib in patients with newly diagnosed CP CML, similar degrees of improvement or preservation of HRQoL were seen in both treatment arms after 12 months [11].…”
Section: Discussionmentioning
confidence: 99%
“…To date, prospective assessment of patient-reported HRQoL in CML trials of most first-and second-generation TKIs has been scarce [7]. However, patient-reported outcome (PRO) data from clinical studies of bosutinib have indicated that patients with CML experienced stable or, in some cases, improved HRQoL during treatment compared with pretreatment status [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Patients reporting their own outcomes have improved control of symptoms, medication adherence, and patient satisfaction. Furthermore, PROs provide distinct prognostic information, exceeding clinical measurements [ 54 - 56 ].…”
Section: Discussionmentioning
confidence: 99%